Does elevation influence mayfly emergence timing? A case study using New Zealand's endemic ephemeropteran fauna. (9th February 2020) - McCulloch, Graham A.; Ingram, Travis; Waters, Jonathan M.
Abstract : 1. The timing of adult emergence in stream insects is tightly constrained by environmental cues. Emergence is therefore predicted to be delayed at higher elevations, although few studies have empirically demonstrated this phenomenon. 2. We analysed the collection records of New Zealand's entire endemic mayfly fauna (52 species, 20 genera, 8 families) to test for correlations between adult emergence timing and elevation. 3. Significant positive associations between emergence timing and elevation were detected in more than half (11/21) of the taxa included in detailed analyses, with emergence delays for individual taxa (mean 3.2 ± 2.6 days per 100 m) similar to those previously observed in other freshwater insect taxa. Interspecific analyses accounting for phylogenetic relatedness revealed a non‐significant positive relationship ( P = 0.14) between median elevation and median collection date. 4. While elevation often has significant effects on insect emergence, these results also emphasise the idiosyncratic responses of individual insect taxa to environmental conditions. More detailed temporal studies are crucial for assessing the ongoing impacts of climate‐driven shifts on insect phenology. Abstract : Collection records of New Zealand's entire endemic mayfly fauna were analysed to test for associations between emergence timing and elevation. More than half of the taxa examined displayed significant positive associations between emergence timing and elevation, with a mean delay of 3.2 days per 100 m of elevation. The influence of elevation on emergence timing varied significantly across species, emphasising the idiosyncratic responses of individual taxa to environmental gradients.